Factors Stimulating Entrepreneurial Success Supported by the Sfax-Innovation 2 Business Incubator - Souissi, Mourad (International Journal of Entrepreneurship and Business Management, 2025)
The Tunisian economy is facing major structural challenges, particularly in the labor market, where there is a persistent mismatch between training and job market needs, as well as high unemployment, especially among young people. According to data from the national agency for employment and self-employment in 2023, the youth unemployment rate in Tunisia was close to 23.7% in the second quarter of 2023, one of the highest in the world (National Institute of Statistics, 2024). To meet these challenges, Tunisia has implemented a number of institutional and governmental initiatives aimed at stimulating investment and promoting employment, notably by supporting entrepreneurship among young graduates. These programs include the Youth Employment Promotion Fund (FOPRODI), the "Startup Act" program, "RAYA" for financial inclusion, "FONAPRA" for the promotion of crafts and small businesses, and "FOSDAP" for agricultural and fisheries development. These schemes aim to encourage innovation, facilitate access to financing and boost the employability of young graduates in an economic context marked by difficult transitions. Our paper aims to identify the key factors for entrepreneurial success in small and medium-sized enterprises (SMEs) in Tunisia, with a focus on young entrepreneurs. To this end, we conducted an exploratory qualitative study with a sample of 14 Tunisian entrepreneurs who had benefited from support at the "Sfax-innovation 2" business incubator in Tunisia. The results reveal that entrepreneurial personality traits, family support, networking and access to financing play a decisive role in entrepreneurial success, according to the testimonies of the entrepreneurs interviewed. These elements highlight the importance of institutional arrangements and social dynamics in the development of SMEs in Tunisia, particularly in a context marked by economic challenges and high youth unemployment.